2003
DOI: 10.1046/j.1365-2362.2003.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vitamin D and calcium status in healthy adult Austrians

Abstract: Prevalence of hypovitaminosis D in adult Austrians is an imminent risk for development of secondary hyperparathyroidism with advancing age, and requires timely correction of nutritional deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
61
2
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 30 publications
13
61
2
5
Order By: Relevance
“…This value compares well with other reports of the vitamin D status in similar latitudes [12, 15, 16] and also with the report of Kudlacek et al [17] about the vitamin D status in the Austrian population. Surprisingly, one study found the average 25-D concentration to be only 4.4 ng/ml (11 nmol/l) although a similar RIA assay was used [18].…”
Section: Discussionsupporting
confidence: 92%
“…This value compares well with other reports of the vitamin D status in similar latitudes [12, 15, 16] and also with the report of Kudlacek et al [17] about the vitamin D status in the Austrian population. Surprisingly, one study found the average 25-D concentration to be only 4.4 ng/ml (11 nmol/l) although a similar RIA assay was used [18].…”
Section: Discussionsupporting
confidence: 92%
“…As there is no consensus on an optimal vitamin D status (Lips, 2004;Dawson-Hughes et al, 2005;Aloia et al, 2006;Bischoff-Ferrari et al, 2006) and no standardization of vitamin D measurement (Lips et al, 1999;Binkley et al, 2004), comparison between different studies and results is rather difficult. However, our data are similar to results of other European studies concerning the prevalence of vitamin D deficiency from various countries in Europe (Burnand et al, 1992;Scharla et al, 1996;Chapuy et al, 1997;Woitge et al, 1998;Lamberg-Allardt et al, 2001;Kudlacek et al, 2003;Ovesen et al, 2003;MacFarlane et al, 2004;Meyer et al, 2004) and other continents (Sherman et al, 1990;Mc Kenna, 1992;Jacques et al, 1997;Looker et al, 2002;Rapuri et al, 2002;Hashemipour et al, 2004;Hanley and Davision, 2005), including countries located at low latitudes (Levis et al, 2005;Lucas et al, 2005). Moreover, studies considerably vary with respect to the recruitment and the age range of the included sample, and only few studies have been based on nationally representative samples (Chapuy et al, 1997;Finch et al, 1998;Looker et al, 2002;Hirani and Primatesta, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…In fact, the levels observed are higher than usually seen in healthy Austrians. 19 Thus, factors other than AED monotherapy may have contributed to the high rates of vitamin D deficiency ⁄ insufficiency or the altered bone turnover reported in earlier studies, [3][4][5][6][7][8] for example the inclusion of participants receiving AED polytherapy 2,8 or those with severe learning disability*, immobility, or cerebral palsy, or other groups at risk for vitamin D deficiency. The last group comprises institutionalized participants, participants with physical disability, low outdoor activity, malnutrition, or a different sociocultural lifestyle, and black participants.…”
Section: Discussionmentioning
confidence: 98%